Acute Migraine Management in Children. Issue 10 (October 2015) - Chen, Lei; Alfonzo, Michael
Abstract : Abstract: Migraines are common, incapacitating, and often stress inducing for pediatric patients and parents alike. According to the Agency for Healthcare Research and Quality, more than 1 million Americans seek emergency care every year due to migraines, with increasing frequency among adolescents. The disease can vary in severity and character, often mimicking life-threatening conditions, requiring prompt nuanced recognition by emergency personnel and implementation of an effective treatment strategy. Development of emergency department guidelines for the management of pediatric migraines should be based on up-to-date evidence supporting safe, appropriate therapies for children.